Analisis Pemilihan Moda Transportasi Untuk Perjalanan Ke Kampus (Studi Kasus: Civitas Akademik Politeknik Negeri Bali) - Fransiska Moi; Ni Putu Indah Yuliana (Universitas Batanghari Jambi, 2022)
In carrying out the daily movement of man from one place to another requires a mode of transportation. In this context, the ownership and use of private and public vehicles can be said to be one of the alternatives for society in meeting the demands of the movement. Specifically in the travel pattern there is information about the characteristics of the traveler and the type of activity of the individual or person per person. Jimbaran area as a tourist area and synonymous with educational institutions and campuses, of course there are many tourist attractions and campuses, one of which is the Bali State Polytechnic. Along with this, research on the preference behavior of the use of student transportation vehicles, aims to analyze the choice of modes on daily trips to PNB, using the Analytic Hierarchy Process method with expert choice software version 11. to find out the most influential factors. The instrument includes a questionnaire form as well as conducting observations and direct interviews with the PNB academic community to identify the characteristics of the PNB academic community in the selection of transportation modes, analyzing the factors that most influence the use of transportation modes, both private vehicles and public vehicles. The results showed that the first priority for undergraduate students at the criteria level was the criteria for getting the highest weight of 36.4% followed by the cost criteria of 34.1%, and finally the safe criteria of 2 9.5%, with an inconsistency value of 0.00096 . From the results of the expert assessment through the questionnaire given, the alternative mode of transportation chosen was motorcycles by 46.4% as the first alternative in the selection of transportation modes, followed by private cars by 35.7% and finally public transportation by 17.9%.